Analisis Peran Push Notification dalam Mendorong Pembelian Peralatan Rokok Elektrik di E-Commerce - Antony, Kevin; Pandrianto, Nigar (Kiwari, 2024)
Technological developments have now made the existence of electric cigarettes increasingly popular, demand for them continues to increase in various countries including Indonesia, as well as developments in information technology such as the internet which have created new marketing techniques, one of these techniques is push notifications, a marketing instrument that can be considered effective. if its existence is able to influence individuals to be interested in the products offered and ultimately make purchasing decisions, therefore this study aims to understand how the role of push notifications influences purchasing decisions for e-cigarette equipment, especially in the Tokopedia application. The research method used to find data is a case study with observation and in-depth interviews as a data collection technique, then the collected data will be processed into interview transcripts. The results of this study indicate that the reaction of each individual in responding to push notifications is found to be different, it depends on their preferences in enabling the feature, besides that this research also shows that push notifications as a marketing tool have an influence on purchasing decisions for Foom products in Tokopedia, however, to make push notifications sent more effective, notifications must be adjusted to user preferences and needs. Perkembangan teknologi kini membuat keberadaan rokok elektrik menjadi semakin populer, peminatnya terus meningkat di berbagai negara termasuk Indonesia, begitu pun dengan perkembangan teknologi informasi seperti internet yang telah menciptakan teknik-teknik marketing baru. Teknik tersebut adalah push notification. Sebuah instrumen marketing dapat dianggap efektif jika keberadaannya mampu memengaruhi individu untuk tertarik pada produk yang ditawarkan dan akhirnya melakukan keputusan pembelian. Maka dari itu, penelitian ini bertujuan untuk memahami bagaimana peran push notification dalam mendorong keputusan pembelian perlengkapan rokok elektrik terkhusus pada aplikasi e-commerce Tokopedia. Metode penelitian yang digunakan untuk mencari data adalah studi kasus dengan observasi dan wawancara mendalam sebagai teknik pengumpulan data. Setelah itu data-data tersebut akan diolah menjadi transkrip wawancara. Hasil penelitian ini menunjukkan bahwa reaksi setiap individu dalam menanggapi push notification ditemukan berbeda-beda, bergantung pada preferensi mereka dalam memfungsikan fitur tersebut. Selain, itu penelitian ini juga menunjukkan bahwa push notification sebagai sebuah alat marketing memiliki pengaruh pada pembuatan keputusan pembelian produk Foom di Tokopedia, namun untuk membuat push notification yang dikirimkan semakin efektif, notifikasi harus disesuaikan dengan preferensi dan kebutuhan pengguna.